KEADILAN ORGANISASIONAL DAN KEPUASAN KERJA: PENGUJIAN KETERKAITAN EQUITY THEORY DENGAN WORK OUTCOMES - Wiyono, Wiyono (Benefit, 2009)
The purpose of this study is to examine relationship between equity theory and work outcomes in educational staffâs context.Â  To operationalize these constructs, equity theory was measured by three dimensions of organizational justice, namely procedural, interactional and distributive justice, while organizational outcome was measured by job satisfaction.Â  The result of study shows that all dimensions of organizational justice have significant effect to job satisfaction. Conclusion about relationship between equity theory and work outcomes and recommendations for future research also discussed.